2005
DOI: 10.1016/j.fmrre.2005.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Flavour formation by lactic acid bacteria and biochemical flavour profiling of cheese products

Abstract: Flavour development in dairy fermentations, most notably cheeses, results from a series of (bio)chemical processes in which the starter cultures provide the enzymes. Particularly the enzymatic degradation of proteins (caseins) leads to the formation of key-flavour components, which contribute to the sensory perception of dairy products. More specifically, caseins are degraded into peptides and amino acids and the latter are major precursors for volatile aroma compounds. In particular, the conversion of methion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
299
0
10

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 728 publications
(349 citation statements)
references
References 146 publications
(209 reference statements)
6
299
0
10
Order By: Relevance
“…Fluctuations in the community members during cheese manufacturing have an effect on the functionality of the starter such as acidification or flavor formation (Smit et al, 2005). Therefore, relative abundance of each genetic lineage during cheese Community stability through genetic diversity O Erkus et al manufacturing was quantified by amplified fragment length polymorphism typing of randomly picked single colony isolates to reveal the community dynamics (Figure 6).…”
Section: Community Dynamics In Cheesementioning
confidence: 99%
“…Fluctuations in the community members during cheese manufacturing have an effect on the functionality of the starter such as acidification or flavor formation (Smit et al, 2005). Therefore, relative abundance of each genetic lineage during cheese Community stability through genetic diversity O Erkus et al manufacturing was quantified by amplified fragment length polymorphism typing of randomly picked single colony isolates to reveal the community dynamics (Figure 6).…”
Section: Community Dynamics In Cheesementioning
confidence: 99%
“…This biodiversity generates particular flavors in these cheeses contributing to the increase in global demand over the last few years (WOUTERS et al, 2002;SMIT;SMIT;ENGELS, 2005). Therefore, the wild strains of lactic acid bacteria (LAB) with particular technological characteristics are really required for new collections for industrial applications.…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…Similar to many other internally bacterial ripened cheeses, Cheddar must be stored at low temperature (5-13°C) for months and sometimes years to attain desired flavor and body attributes. During this period, microorganisms and enzymes trapped in the cheese matrix act on curd substrates in a manner that is heavily dictated by the curd microenvironment (e.g., cheese pH, water activity, salt content, redox potential, and temperature), producing a heterogeneous mixture of volatile and nonvolatile flavor and aroma compounds that eventually confer mature cheese flavor (Fox et al, 1993;Fox and Wallace, 1997;Marilley and Casey, 2004;Smit et al, 2005;Ardö, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Given the causal role of LAB in cheese flavor development, research to define the biochemical basis for flavor changes in cheese has logically focused on the microbiology and physiology of species present in cheese (for reviews, see Beresford et al, 2001;Marilley and Casey, 2004;Smit et al, 2005;Ardö, 2006;Broadbent and Steele, 2007;Cogan et al, 2007;Drake, 2007). Those efforts have identified several important biochemical and chemical processes that occur during maturation, and demonstrated that starters, adjuncts, and NSLAB can have an intimate role in those processes.…”
Section: Introductionmentioning
confidence: 99%